Effective dopants in p-type elementary Te thermoelectrics. Issue 29 (22nd March 2017) - Qian, Xin; Xiao, Yu; Zheng, Lei; Qin, Bingchao; Zhou, Yiming; Pei, Yanling; Yuan, Bifei; Gong, Shangkai; Zhao, Li-Dong
Abstract : Bi and Sb are effective dopants in a p-type Te system and can largely enhance the thermoelectric performance of Te, the maximum ZT values of ∼0.8 in Te0.9925 Bi0.0075 and ∼1.1 in Te0.985 Sb0.015 at 673 K can be achieved. Abstract : Elementary Te is predicted to be a high-performance thermoelectric material through theoretical calculation, and the experimental results have confirmed this prediction through optimizing carrier concentrations. In this work, we investigate the thermoelectric transport properties in undoped Te at 300–673 K, revealing a low thermal conductivity ∼1.8 W m −1 K −1 at room temperature and a ZT ∼ 0.2 at 653 K. To further improve the thermoelectric performance in the Te system, we choose Sn, Pb, Bi, and Sb as dopants in Te. We find Bi and Sb can effectively enhance the electrical conductivity by two orders, from ∼2 S cm −1 in undoped Te to ∼300 S cm −1 and ∼550 S cm −1 at 300 K in Bi-doped and Sb-doped samples respectively. Meanwhile, these dopants can simultaneously significantly suppress the lattice thermal conductivity, decreasing from 1.22 W m −1 K −1 in undoped Te to 0.68 W m −1 K −1 and 0.73 W m −1 K −1 at 673 K in Bi-doped and Sb-doped samples, respectively. Maximum ZT values of ∼0.8 in Te0.9925 Bi0.0075 and ∼1.1 in Te0.985 Sb0.015 at 673 K can be achieved. The results indicate that Sb is an effective dopant in the Te system.